THE DESCRIPTION OF KNOWLEDGE, PERCEPTION, ROLE, ROLE IMPLEMENTATION, EMOTIONAL CONNECTION IN PSYCHOSEXUAL DEVELOPMENT OF CHILDREN AGED 3-5 YEARS IN NEW NORMAL PERIOD AT THE SUBURBAN OF SURABAYA - Elly Dwi Masita; Adenia Dwi Ristanti (Jurnal Ilmu Keperawatan dan Kebidanan, 2021)
The number of pornography and cybercrime among Indonesian children reaches 4448 cases – children as a perpetrator and victim. Meanwhile, Indonesian children experience 183 cases of rape and sexual abuse, 54 cases of sodomy or pedophilia – children as a perpetrator, 42 cases of sodomy or pedophilia – children as a victim, and 44 cases of abortion. Preliminary study on March 2020 in West Surabaya showed that 6 in 10 children aged 3-5 years faced sexual abuse or harassment and rape by their closest circle. The research aims are to describe the level of knowledge, perception, role implementation, emotional connection between father and child in the accompaniment of psychosexual development of children. This paper combined quantitative and qualitative methodologies with a phenomenological approach. Respondents were father compatible with inclusion criteria – was determined by researchers. This study used total sampling – 112 fathers lived in West Surabaya. The research instruments were questionnaire and observation sheet. Data analysis utilized percentage analysis, data reduction, and data triangulation.Result: There were 64.5% low level of knowledge, 70.5% negative perception, 63.4% father absence in assisting psychosexual development of children, and 69.6% absence of emotional connection.Conclusion: The father’s role in assisting the psychosexual development of children aged 3-5 years can decrease the number of psychosexual disorders in adulthood.Keywords: knowledge, perception, role, role implementation, father, child’s psychosexual